Post-radiation oxidation reaction of three types of polyethylene films - HAN Lei; WANG Jing; LU Manli; ZHANG Wenli; SHEN Rongfang; LIU Weihua; WANG Mouhua (Fushe yanjiu yu fushe gongyi xuebao)
The long-term, slow reaction that occurs when polyethylene (PE) is exposed to oxygen after ionizing radiation is known as post-radiation oxidation, which significantly affects the long-term performance of radiation-modified PE materials. In this study, an ultrahigh molecular weight polyethylene (UHMWPE) film, a high-density polyethylene (HDPE) film, and a low-density polyethylene (LDPE) film were selected as typical PE materials and irradiated with γ-rays. Subsequently, the carbonyl products of the post-radiation slow oxidation reaction were quantitatively analyzed using Fourier transform infrared spectroscopy and by varying the temperature, oxygen partial pressure, and absorbed dose. The effects of these factors on the oxidation behavior of PE after radiation were systematically investigated. Post-radiation oxidation was clearly observed in the UHMWPE and HDPE films. Meanwhile, the LDPE film showed weak post-radiation oxidation, which could be maintained for a long time at room temperature, with the highest reaction rate occurring at 50 °C. However, above 70 °C, the oxidation reaction could only be maintained for a few hours. Additionally, a significant positive correlation was observed among the post-radiation oxidation reaction, oxygen partial pressure, and absorbed dose. This study not only offers a new perspective for understanding the post-radiation oxidation reaction of PE but also provides guidance for improving the accelerated-aging evaluation of radiation-modified PE materials.